UPAYA GUEST RELATION OFFICER (GRO) DALAM MELAYANI TAMU MEMBER ACCOR DI FRONT OFFICE DEPARTEMENT HOTEL MERCURE PONTIANAK KALIMANTAN BARAT - Winda Rosita Dewi; Resti (AKPARDA, 2025)
This research discusses how the service procedures of a guest relation officer (GRO) at Mercure Hotel Pontianak West Kalimantan and how the guest relation officer's efforts in handling very important person (VIP) guests at Mercure Hotel Pontianak. This research method used qualitative descriptions, namely descriptive statistics with the research subject was Guest Relation Officer with Accor Membership guests. Data collection methods were obtained through observation, interviews, documentation, and literature study. The results of this study indicate that the higher the level of service provided by front office staff, the more positive the guest experience in enjoying the services at the hotel. The main factors that contribute to the success of front office services are interpersonal skills, the ability to understand guest needs, and the implementation of operational standards properly.